Implementation of virtual consultation between primary and secondary health care in a third-level hospital (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
Objectives: To evaluate the usefulness of the implementation of telematic consultation between primary and secondary health care in a third-level hospital.Methods: A descriptive analysis of the telematic consultation between primary care and Urology. Including all consultations of patients over 16 years old, for a period of 27months.Results: 11824 telematic consultations were evaluated with an average of 438 per month. 395 general practitioners participated. 18% of the consultations were resolved online. The response delay did not exceed 96h in 86% of cases.Conclusions: It represents the future in communication between primary and secondary care. Allowing to reduce the referrals to the specialist and giving a quick and adequate response.